Energy model as a sustainable function in building design decisions - Murti, Farida; Utomo, Christiono (2008)

(untitled)
New buildings display an increasing awareness of sustainability but invariability assume a level of technical sustainability an concentrate on economic and social sustainability, as opposed to environmental sustainability. This paper presents an approach and study to describe and modeling energy as a sustainable function in building design decisions. The object study is a big mall (under pre construction-delayed) in a new district in Surabaya, Indonesia. With the cost of energy rising and availability decreasing the need to provide energy-efficient design become more important. As a proponent of increased value, our knowledge of energy must be expanded. Source of energy and the availability of energy must be understood. This is a consideration to the design life of project, consumption rates, equipment efficiencies, system design and other factors that contribute to waste energy. A means of accounting for the energy uses for the construction and operation of building and plant facilities is needed. More specially, it is necessary to know the areas within a building which are energy consumer and to learn how much energy a building uses as a comparison to the amount of energy that a building should use. Commencing at the design and planning stage, the technical, social, economic and environmental sustainability of building energy of a mall development needs to be considered. The decision building design consists of three sustainability functions that are economic sustainability, environment and social sustainability and technical sustainability. Combining of three functions have built a set of decision hierarchy in a model of Analytical Hierarchy Process (AHP). Analysis from decision process revealed model of energy in the project.